1994
DOI: 10.1136/jnnp.57.9.1057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vigabatrin on partial seizures and cognitive function.

Abstract: In comparison with the baseline period, vigabatrin treatment was associated with a significant reduction in median complex partial seizure frequency four to 12 and 12 to 20 weeks after commencing vigabatrin (-66% and -69% in the vigabatrin group, + 50% and + 25% in the placebo group). Ten of 20 patients on vigabatrin and four of 23 on placebo showed a > 50% reduction in complex partial seizure frequency in the last eight weeks of double blind treatment. At least 60% of responders had maintained the response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…Vigabatrin had no detrimental effects on cognitive functions at 12 months, and memory retrieval and mental flexibility improved significantly. One double-blind, placebo-controlled, randomized study reported impaired performance relating to motor speed and design learning in adolescents and adults with partial epilepsy [Grunewald et al 1994]. However, such negative effects were only reported in nonresponders who poorly tolerated the drug.…”
Section: Vigabatrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Vigabatrin had no detrimental effects on cognitive functions at 12 months, and memory retrieval and mental flexibility improved significantly. One double-blind, placebo-controlled, randomized study reported impaired performance relating to motor speed and design learning in adolescents and adults with partial epilepsy [Grunewald et al 1994]. However, such negative effects were only reported in nonresponders who poorly tolerated the drug.…”
Section: Vigabatrinmentioning
confidence: 99%
“…These include refractory cases, patients with different kinds of epilepsy and younger or older patients. One study of vigabatrin reported CAEs in a relatively limited set of individuals classified as nonresponders [Grunewald et al 1994], although the characteristics of these individuals were poorly specified. Improvements in seizure control are particularly important in relation to attributing the cause of positive effects on cognition.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Six crossover studies 49,54,83,[85][86][87] and four parallel studies 38,[153][154][155] compared adjunctive VGB with placebo in patients with refractory seizures. In all but four of the trials, which involved patients with both generalised and partial seizures, 54,83,85,86 all patients had partial seizures.…”
Section: Figure 18 Proportion Of 50% Responders (Unpooled Rrs 95% CImentioning
confidence: 99%
“…However, details were lacking in 16 studies and four failed to provide details. [38][39][40] Two of these studies were only published in abstract form. 40,41 2.…”
mentioning
confidence: 99%
“…In another parallel-group study of GBP, seizures in 5 of 18 patients taking placebo worsened during the treatment period (32). Similarly, increases in seizure frequency >50% were recorded in the placebo arms of trials of LTG (33) and VGB (34). Regression to the mean (or to the median) appears to be the most frequent reason for observed increases in seizure frequency in studies of the "before-and-after'' design (35).…”
mentioning
confidence: 99%